Thermal Management of Flat Photovolatic Panels using Serrated Fins to Increase Electrical Output - Chandrasekar, M.; Priyan, C. Kirthi (Journal of Technology Innovations in Renewable Energy, 2018)
The electrical power output of photovoltaic (PV) cell depends on its operating temperature during its absorption of solar radiation and conversion of solar energy to electrical energy. The increase in PV panel temperature due to overheating negates its electrical yield and efficiency. In addition, overheating causes hot spots, failure of adhesive seals and delamination. An effective way to combat this problem is to reduce the operating temperature of PV panel by cooling. In the present work, a novel thermal management technique for improved cooling of flat PV panel is proposed with the use of serrated fins rather than straight fins. For this reason, the thermal and electrical performance of the flat PV panel with cooling system consisting of duct, brushless DC cooling fan, a plate fin and serrated fins of varying angles (30o, 45o and 60o) made up of aluminium were investigated experimentally. Experiments were conducted at constant wind velocity (1 m/s) with the developed technique in the location of Tiruchirappalli (78.6 E to 10.8 N), Tamil Nadu, India with flat 10 W PV panel. By using serrated fins of varying angles of 30o, 45o, 60o and plate fin (90°), the temperature of the PV panel decreased by a maximum of 4oC, 7oC, 6oC and 3oC respectively. Similarly the PV power increased in the range of 15.38%, 61.53%, 41.53% and 7.69% for 30o, 45o, 60o and plate fin (90°) respectively. It is concluded that 45o angled serrated fin is more efficient in providing the cooling effect than the other angles of serrated fins considered.